High‐speed photoacoustic microscopy of mouse cortical microhemodynamics. Issue 6 (23rd December 2016) - Lin, Li; Yao, Junjie; Zhang, Ruiying; Chen, Chun‐Cheng; Huang, Chih‐Hsien; Li, Yang; Wang, Lidai; Chapman, William; Zou, Jun; Wang, Lihong V.
Abstract : We applied high‐speed photoacoustic microscopy (PAM) for both cortical microenvironment studies and dynamic brain studies, with micrometer‐level optical resolution and a millisecond‐level cross‐sectional imaging speed over a millimeter‐level field of view. We monitored blood flow redistribution in mini‐stroke mouse models and cerebral autoregulation induced by a vasoactive agent. Our results collectively suggest that high‐speed PAM is a promising tool for understanding dynamic neurophysiological phenomena, complementing conventional imaging modalities. Abstract : We present a high‐speed optical‐resolution photoacoustic microscopy (OR‐PAM) with micrometer‐level resolution and a millisecond‐level cross‐sectional imaging speed over a millimeter‐level field of view. Using this high‐speed OR‐PAM, we quantified the blood flow redistribution in response to spontaneous microhemorrhage, as well as to laser induced occlusions of single microvessels. We also imaged cerebral autoregulation on single microvessels in an intact mouse brain.